Helping struggling learners of English as an additional language succeed with interactive multisensory structured strategies - Schneider, Elke; Kulmhofer, Andrea (BELT - Brazilian English Language Teaching Journal, 2016)
Based on cross-linguistic and interdisciplinary research of several decades that bridges learning an additional language with the field of learning differences/disabilities, this article shares research-evidenced practices to effectively address the needs of struggling foreign and second language learners of English in Brazil. These multisensory structured strategies enhance pronunciation, listening, reading and writing skills and strengthen grammar and vocabulary competencies of struggling learners. The selected multisensory structured metacognitive strategies can easily be infused into existing English as a foreign/second language curricula.